Information Systems Success and User Acceptance in Digital Tax Transformation: A Systematic Literature Review - Gede Angga Ardiana; Milla Sepliana Setyowati (Information System Study Program, Faculty of Engineering and Vocational, Undiksha, 2026)
Digital transformation in tax administration often faces structural challenges due to the fragmentation between information system success and user acceptance research. This study aims to synthesize the existing literature and develop an integrative conceptual framework for digital tax administration transformation. Using a Systematic Literature Review (SLR) approach, 26 Scopus-indexed articles published between 2021 and 2026 were analyzed following the PRISMA protocol and quality assessment procedures. The findings indicate that system quality, information quality, service quality, and trust are key factors shaping perceived usefulness, user satisfaction, and technology adoption. The literature further suggests that sustained system use is associated with improved tax compliance, organizational benefits, and broader digital transformation outcomes. In addition, digital literacy, organizational readiness, top management support, and change management were identified as important contextual factors. The study concludes that digital tax system success cannot be understood solely from either technical or behavioral perspectives. Its primary contribution is the development of an Integrated Framework of Digital Tax Transformation Success that conceptually links system success, user acceptance, tax compliance, and digital transformation outcomes within a unified framework.